Model reduction of unstable systems based on balanced truncation algorithm - Ngoc Kien Vu; Hong Quang Nguyen (Institute of Advanced Engineering and Science, 2021)
Model reduction of a system is an approximation of a higher-order system to a lower-order system while the dynamic behavior of the system is almost unchanged. In this paper, we will discuss model order reduction (MOR) strategies for unstable systems, in which the method based on the balanced truncation algorithm will be focused on. Since each MOR algorithm has its strengths and weakness, practical applications should be suitable for each specific requirement. Simulation results will demonstrate the correctness of the algorithms.